Expert System to Diagnose Human Heart Disease Using Web-Based Forward Chaining Method: Expert System to Diagnose Human Heart Disease Using Web-Based Forward Chaining Method - Doddy Prasetyo; M Iwan Wahyuddin; Ratih Titi Komalasari (Jurnal Mantik, 2020)
People do not realize that the heart is an organ that plays an important role in the circulatory system, and are very dangerous if the heart is experiencing problems or disturbances. But there are still many people who do not know the symptoms caused when the heart is having problems. In fact one of the causes of high mortality in Indonesia is due to heart disease. The purpose of this study is done to provide an update to the user to know the symptoms of heart disease as well as solutions. The method used in this study, is to use the Forward Chaining method. Expert systems will be created using PHP and MySQL database driven website.